UJI AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL BIJI NANGKA (Artocarpus heterophyllus Lam.) TERHADAP STABILISASI MEMBRAN SEL DARAH MERAH - Wahdaniah, Wahdaniah; Sabrina Azani, Aulia; Kamilla, Laila (Jurnal Laboratorium Khatulistiwa, 2023)
Jackfruit seed (Artocarpus heterophyllus Lam.) is local plant that contains compounds such as flavonoids, saponins and steroids that have potential as antiinflammatory. This research aims to determine the difference in antiinflammatory activity of ethanol extract jackfruit seed (Artocarpus heterophyllus Lam.) from sodium diclofenac on red blood cell membrane stability. Antiinflammatory activity can be seen from the decrease in absorbance of hemoglobin lysed in test solution after being induced by hypotonic solution and compared with the positive control (sodium diclofenac). This research is a quasi experiment with the method of red blood cell membrane stability in vitro using purposive sampling technique with samples of ethanol extract jackfruit seed concentrations of 0,005%, 0,01%, 0,02% and 0,04% which were repeated 3 times. The results showed that ethanol extract jackfruit seed (Artocarpus heterophyllus Lam.) has the ability to stabilize red blood cell membrane with a percent stability at concentration of 0,005% is 41,70%, concentration of 0,01% is 50,70%, concentration of 0,02% is 54,20% and concentration of 0,04% is 64,60%. The antiinflammatory activity of ethanol extract jackfruit seed 0,02% is not different from sodium diclofenac 0,005% with p value > 0,05, whereas ethanol extract jackfruit seed 0,005%, 0,01% and 0,04% are different from sodium diclofenac.